2022
DOI: 10.1183/13993003.02806-2021
|View full text |Cite
|
Sign up to set email alerts
|

Acute exacerbation of idiopathic pulmonary fibrosis after SARS-CoV-2 vaccination

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection has spread worldwide and coronavirus disease 2019 remains a top health concern. Several SARS-CoV-2 vaccines have been produced and are playing great roles in the prevention of infection and worsening to a severe state, and in improving mortality [1]. However, some concerns about adverse effects related to SARS-CoV-2 vaccination have been raised. Recently, various adverse effects have been reported, but there is little data on adverse effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 11 publications
4
17
0
Order By: Relevance
“…Myall et al reported that some COVID‐19 patients experience persisting symptoms and OP pattern pneumonitis, 8 and judging from the clinical course of the cases reported here, BAL results and pathological results (in the second case only), perhaps the major pathophysiology could have been recurrent OP rather than AE‐ILD. The latter implies the possibility of AE‐ILD, as we recently reported in a case study of AE of underlying fibrotic ILD 9 . A similar case has been reported by Ghincea et al 10 The first patient here is suspected to have had pre‐existing ILD and in the second patient, a previous chest x‐ray showed reticulation in the lower lung fields, which raised the possibility of AE of RA associated with ILD.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Myall et al reported that some COVID‐19 patients experience persisting symptoms and OP pattern pneumonitis, 8 and judging from the clinical course of the cases reported here, BAL results and pathological results (in the second case only), perhaps the major pathophysiology could have been recurrent OP rather than AE‐ILD. The latter implies the possibility of AE‐ILD, as we recently reported in a case study of AE of underlying fibrotic ILD 9 . A similar case has been reported by Ghincea et al 10 The first patient here is suspected to have had pre‐existing ILD and in the second patient, a previous chest x‐ray showed reticulation in the lower lung fields, which raised the possibility of AE of RA associated with ILD.…”
Section: Discussionsupporting
confidence: 79%
“…The latter implies the possibility of AE-ILD, as we recently reported in a case study of AE of underlying fibrotic ILD. 9 A similar case has been reported by Ghincea et al 10 The first patient here is suspected to have had pre-existing ILD and in the second patient, a previous chest x-ray showed reticulation in the lower lung fields, which raised the possibility of AE of RA associated with ILD. Post-COVID-19 ILD should also be considered when discussing this, although such cases sometimes improve over time and it is questionable whether these two cases had chronic fibrotic ILD at the moment of vaccination.…”
Section: Discussionsupporting
confidence: 78%
“…Surprisingly, some cases of acute exacerbation after COVID-19 vaccination have been described in ILDs. 191 , 192 , 193 The benefit of vaccination is over the potential side effects of the vaccine, but physicians must monitor closely those patients that present respiratory worsening after vaccination.…”
Section: Interstitial Lung Diseasesmentioning
confidence: 99%
“…Similarly, a potential association of AE and the first dose of an mRNA COVID-19 vaccination has recently been observed in a 72-yr old male IPF patient successfully treated with glucocorticoids [ 8 ]. This association has further been confirmed by the case of a 84-yr old male patient affected by f-ILD after receiving the second of an mRNA vaccine [ 9 ]. In line with these previous observations, our findings reinforce the triggering role of anti-COVID-19 vaccination on ILD progression suggesting that such an adverse event may occur even later and despite the patient well tolerated the first two doses of immunization.…”
Section: Discussionmentioning
confidence: 70%